2019
DOI: 10.1088/2515-7620/ab37fd
|View full text |Cite
|
Sign up to set email alerts
|

Trees in cool climate cities may increase atmospheric carbon by altering building energy use

Abstract: Urban trees are a critical part of the 'green infrastructure' intended to make our growing cities more sustainable in an era of climate change. The potential for urban trees to modify microclimates and thereby reduce building energy use and the associated carbon emissions is a commonly cited ecosystem service used to justify million tree planting campaigns across the US. However, what we know of this ecosystem service comes primarily from unvalidated simulation studies. Using the first dataset of actual heatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…-Empirical Outcomes: Only 17% of survey respondents said that research has been conducted to assess whether stated benefits of the TPI have been realized. This illuminates an important research gap in urban greening scholarship, especially in light of studies that raise questions about the capacity of urban trees to meet various ecosystem function/service goals (e.g., Pataki et al, 2011;Nelson et al, 2012;Pincetl et al, 2013;Petri et al, 2017;Eisenman et al, 2019;Erker and Townsend, 2019;Xing and Brimblecombe, 2019). Yet the rise of urban TPIs over the past decade also points to compelling opportunities for empirical research and natural experiments on a range of environmental outcomes including air quality, local and citywide temperature, atmospheric carbon, hydrology, and wildlife; human health outcomes based on epidemiological methods; and psychosocial metrics related to stress, mental health, social cohesion, and crime.…”
Section: Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…-Empirical Outcomes: Only 17% of survey respondents said that research has been conducted to assess whether stated benefits of the TPI have been realized. This illuminates an important research gap in urban greening scholarship, especially in light of studies that raise questions about the capacity of urban trees to meet various ecosystem function/service goals (e.g., Pataki et al, 2011;Nelson et al, 2012;Pincetl et al, 2013;Petri et al, 2017;Eisenman et al, 2019;Erker and Townsend, 2019;Xing and Brimblecombe, 2019). Yet the rise of urban TPIs over the past decade also points to compelling opportunities for empirical research and natural experiments on a range of environmental outcomes including air quality, local and citywide temperature, atmospheric carbon, hydrology, and wildlife; human health outcomes based on epidemiological methods; and psychosocial metrics related to stress, mental health, social cohesion, and crime.…”
Section: Future Researchmentioning
confidence: 99%
“…Related studies have addressed factors that influence residents' participation in TPIs (Locke et al, 2015;Hand et al, 2019), and how such participation influences urban tree canopy patterns (Locke and Morgan Grove, 2014). Others have assessed links between TPIs, canopy cover, income, race, and ethnicity (Watkins et al, 2017), as well as links to residential energy use (Nelson et al, 2012;Ko et al, 2015b;Erker and Townsend, 2019), carbon sequestration and hydrology (Pincetl et al, 2013), carbon life cycle (McPherson and Kendall, 2014), and emission of biogenic volatile organic compounds (Curtis et al, 2014). Of note, numerous studies have assessed the tree survival rates of TPIs and associated links to biophysical and sociopolitical factors (Oldfield et al, 2013;Koeser et al, 2014;Mincey and Vogt, 2014;Roman et al, 2014;Ko et al, 2015a;Roman et al, 2015;Vogt et al, 2015a,b;Widney et al, 2016;Blair et al, 2019;Breger et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Johnson et al (2018) found that legacies of land use matter for modern biodiversity, whereby the type of past industrial land use influences the species found on brownfields. Indeed, in most studies the authors acknowledged that results are context‐specific and not necessarily generalizable (Erker & Townsend, 2019; Larson et al, 2016; Nesbitt et al, 2017). Understanding the ecological, social, and cultural context of a place is critical to understanding outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, besides climate change, soaring urbanization have expanded our need to make cities more sustainable. Urban trees are often advocated as a means to that end (Erker and Townsend, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Urban trees are strategic components of the green substructure envisioned to make our growing cities more ecological in this period of climate change (Erker and Townsend, 2019). Estimation of carbon storage by tropical trees in municipal environments would be beneficial for evaluating environmental and economic benefits of the ecosystems.…”
Section: Introductionmentioning
confidence: 99%